Improving Students’ Mental Model of Newton’s Third Law: Local Wisdom, Modeling Cycle, and Problem-Based Learning - Dinata, Pri Ariadi Cahya; Setiaji, Bayu; Sari, Desy Kumala; Hartanto, Theo Jhoni (STKIP Singkawang, 2025)
Students need a proper mental model to advance mastery of physics and understand the application of the concept of science. Therefore, it is necessary to research how to improve students' mental models based on Newton's third law, which integrates modeling cycles into problem-based learning. As an anchor of learning, the students were asked to explain action and reaction forces and their effects on Borneo’s local wisdom, balogo, and jukung barenteng. The research method used was quasi-experimental with a pretest-posttest control group design. The samples included 87 students of the 10th class in SMAN 1 Kelua and MAN 2 Tabalong. The essay test obtained students' mental models and was analyzed using N-Gain and a one-way ANOVA. The data analysis showed that every class has an average gain, and the p-value for the post-test score is less than 0.05. This means significant differences exist between students' post-test scores in the experimental class and students' post-test scores in the control class. It is indicated that problem-based learning with the modeling cycle and problems of balogo and jukung barenteng improves students' mental model of Newton's Third Law. Integrating local cultural elements such as balogo and jukung barenteng fosters deeper conceptual comprehension and offers an effective method for contextualizing abstract physics concepts through real-world examples. These learning strategies could be applied to other physics topics to improve students’ mental models and learning engagement.